2013
DOI: 10.1002/gps.3993
|View full text |Cite
|
Sign up to set email alerts
|

Piloting and validation of a novel self‐administered online cognitive screening tool in normal older persons: the Cognitive Function Test

Abstract: The online CFT was shown to be suitable for self-administration in online format (with a mouse response mode) for this midlife age group. Individuals may wish to monitor their cognitive performance before memory concerns are sufficient to warrant visiting a GP or memory clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…This is in the high end of previous reports. The CSI memory factor had a .52 correlation to the Buschke Selective Reminding Test (Erlanger et al, 2002 ), CFT episodic memory recognition had a .39 correlation to Total Doors and People, and CFT episodic memory recall had a .43 correlation to People recall (Trustram Eve & de Jager, 2014 ). One study found the CogState One-Back and Learn tasks to correlate .54 and .83 to the Brief Visual Memory Test (Maruff et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in the high end of previous reports. The CSI memory factor had a .52 correlation to the Buschke Selective Reminding Test (Erlanger et al, 2002 ), CFT episodic memory recognition had a .39 correlation to Total Doors and People, and CFT episodic memory recall had a .43 correlation to People recall (Trustram Eve & de Jager, 2014 ). One study found the CogState One-Back and Learn tasks to correlate .54 and .83 to the Brief Visual Memory Test (Maruff et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally these batteries require a test administrator—for example, CNS Vital Signs (Gualtieri & Johnson, 2006 ) and Cognitive Stability Index (CSI; Erlanger et al, 2002 ). Still, some batteries are completely self-administered—for example, Cognitive Function Test (CFT; Trustram Eve & de Jager, 2014 ), Computerized Self Test (COGselftest; Dougherty et al, 2010 ), and CogState (Hammers et al, 2012 ; Maruff et al, 2009 ). Although being completely self-administered, several web-based test systems seem to lack features making them optimal for organized large-scale assessment, such as an administrative user interface for designing, deploying, and monitoring assessments.…”
mentioning
confidence: 99%
“…As suggested by others [31], the mean value plus 1 SD was used as cutoff for one group with good DS performance and another group with poor DS performance. The mean values of the DS and the wBCST for both groups were calculated and the significance of the differences was calculated using a non-parametric Mann-Whitney U-test.…”
Section: Methodsmentioning
confidence: 99%
“…AlzU.org has been shown to significantly improve medical knowledge about AD prevention and improve willingness to participate in an AD prevention clinical trial (15). AlzU.org also contains a number of activities, including the option to take online cognitive tests which may be particularly useful for detecting and longitudinally assessing prodromal pathological changes due to AD (i.e., Cognitive Function Test (16) and Neurotrack (17)) in an easily accessible online format. Currently, AlzU.org provides 6 evidence-based interactive lessons (~10 minutes each) and 12 activities (e.g.…”
Section: Applying the Conceptual Frameworkmentioning
confidence: 99%